MEASURES AND PROSPECTS FOR THE DEVELOPMENT OF THE INTERNAL AUDIT SYSTEM IN THE FUEL INDUSTRY IN UZBEKISTAN - Jalilov Isfandiyor Khudoyorovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article considers the procedure for the development and solution of a number of methodological and organizational and technical problems in the implementation of internal audit of the organization. Proposals will be made to further improve the conditions for the development of the market of audit services and the introduction of modern approaches to the regulation of auditing in accordance with international standards.